The Role of Influencers on Marketing Strategies in The Digital Era: A Literature Study - Rahayu Lestari; Kumba Digdowiseiso; Siti Falindah Padlee (CV ODIS, 2023)
This research investigates the role of influencers in marketing strategies in the digital era. The background is a profound transformation in consumer behavior and marketing influenced by developments in digital technology. Influencers, who have large and engaged followings on social media platforms, have become an important element in companies' marketing efforts to reach target audiences and build brands. The aim of this research is to understand the extent to which influencers influence consumer behavior, increase brand awareness and influence purchasing decisions in the context of digital marketing. The research method uses a literature review with a qualitative approach. The results of this research reveal that influencers have a significant impact in influencing consumer perceptions of brands and products, with the majority of respondents admitting that they trust influencer recommendations in their purchasing decisions. In addition, content produced by influencers is considered to have added value in the form of useful information and interesting entertainment. This supports the view that influencers play an important role in digital marketing strategies with the potential to achieve diverse marketing objectives, from increasing brand awareness to increasing interactions with consumers.